Renal effects of norepinephrine‐induced variations in mean arterial pressure after liver transplantation: A randomized cross‐over trial. Issue 9 (12th June 2018) - Skytte Larsson, J.; Bragadottir, G.; Redfors, B.; Ricksten, S.‐E.
Abstract : Background: Acute kidney injury is commonly seen after liver transplantation. The optimal perioperative target mean arterial pressure (MAP) for renal filtration, perfusion and oxygenation in liver recipients is not known. The effects of norepinephrine‐induced changes in MAP on renal blood flow (RBF), oxygen delivery (RDO2 ), glomerular filtration rate (GFR) and renal oxygenation (=renal oxygen extraction, RO2 Ex) were therefore studied early after liver transplantation. Methods: Ten patients with an intra‐ and post‐operative vasopressor‐dependent systemic vasodilation were studied early after liver transplantation during sedation and mechanical ventilation. To achieve target MAP levels of 60, 75 and 90 mm Hg, the norepinephrine infusion rate was randomly and sequentially titrated. At each target MAP, data on cardiac index (CI), RBF and GFR were obtained by transpulmonary thermodilution (PiCCO), the renal vein thermodilution technique and renal extraction of chromium ethylenediaminetetraaceticacid ( 51 Cr‐EDTA), respectively. Renal oxygen consumption (RVO2 ) and extraction (RO2 Ex) were calculated according to standard formulas. Results: At a target MAP of 75 mm Hg, CI (13%), RBF (18%), RDO2 (24%), GFR (31%) and RVO2 (20%) were higher while RO2 Ex was unchanged compared to a target MAP of 60 mm Hg. Increasing MAP from 75 up to 90 mm Hg increased RVR by 38% but had no further effects on CI, RBF, RDO2 or GFR. Conclusions: In patients undergoing liver transplantation, RBF and GFR are pressure‐dependent at MAP levels below 75 mm Hg. Our results suggest that MAP should probably be targeted to approximately 75 mm Hg for optimal perioperative renal filtration, perfusion and oxygenation in patients undergoing liver transplantation.